Engaging the Lebanese diaspora: Socioeconomic determinants, barriers, and opportunities for sustainable development - Omar, Maha Haj (Edelweiss Applied Science and Technology, 2025)
This article studies the contributions of Lebanese expats to the country’s socioeconomic and cultural aspects, focusing on the main factors influencing financial and non-financial engagement of the diaspora, such as generational differences, financial ability, and cultural links. This research drew data from the Lebanese Diaspora Online Survey (LDOS), which included 123 respondents. The study finds that generational differences, financial capacity, and cultural connections significantly influence the level of engagement of Lebanese expatriates. Systemic constraints, such as institutional mistrust and political instability, are identified as the main reasons for the lack of financial engagement from expatriates. The study concludes that Lebanese expatriates are a crucial factor in Lebanon’s economic and cultural development, but the current political and institutional landscape limits their financial contributions. Structural reforms are essential to improve diaspora engagement and maximize their potential for national growth. A comparative review of multinational diaspora models provides actionable ideas, including centralized engagement structures and diaspora-focused investment channels. The findings showcase the criticality of structural reforms to maximize the diaspora’s potential and long-term financial national growth.